Ultrasound guided quadratus lumborum (QL) block versus transversus abdominis plane (TAP) block for multimodal postoperative analgesia after total abdominal hysterectomy - Mohd Fakhri Hilmi Danial (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Introduction: Truncal blocks play an important role in multimodal analgesia techniques in abdominal surgery. The transversus abdominis plane (TAP) block is a well-known abdominal wall block and the quadratus lumborum (QL) block is a new abdominal truncal block used for somatic analgesia in both upper and lower abdomen. In this prospective, randomized, interventional study, we aimed to compare the QL block and TAP block for postoperative pain after total abdominal hysterectomy. Methods: 30 patients undergoing total abdominal hysterectomy were randomized into 2 groups: QL block and TAP block groups. All blocks were performed under general anesthesia at the end of surgery and the candidates in both groups received 0.375% 20ml ropivacaine each side. All patients received patient-controlled analgesia morphine, celecoxib and paracetamol as postoperative analgesia. Postoperative cumulative morphine requirement, pain score at rest and pain score on movement were assessed across time postoperatively. Results: Patients in the QL block group showed a statistically significant reduction in cumulative morphine consumption at 12, 24, 36 and 48 hours postoperatively compared to the TAP block group after total abdominal hysterectomy (p value: 0.043). However, this study was unable to prove effectiveness between the TAP block and QL block groups in decreasing postoperative pain score at rest (p value: 0.614) and pain score on movement (p value: 0.280) following total abdominal hysterectomy. Conclusion: In summary, the QL block only showed statistically significance in terms of reduction in cumulative morphine consumption postoperatively compared to the TAP block following total abdominal hysterectomy.